Financial literacy in SMEs: a bibliometric analysis and a systematic literature review of an emerging research field. - Molina-García, Jorge Antonio; Diéguez-Soto, Julio; Galache-Laza, María Teresa; Campos-Valenzuela, Marta (Springer Nature, 2022)
Research on financial literacy in small and medium enterprises (SMEs) has raised a significant amount of interest in recent years and has evolved both rapidly and unevenly. This paper is the first to provide a reliable, consistent, and up-to-date review of financial literacy in SMEs through the combination of a bibliometric analysis and a systematic literature review. Specifically, and after identifying the most influential agents involved in this field of research, we carried out a co-occurrence analysis of the authors’ keywords, co-citation analysis of the cited references and a subsequent in-depth analysis of a total of 88 documents published between 2005 and 2020. The findings indicate that SME financial literacy research has been primarily analysed regarding the following topics: (1) performance, (2) access to finance, (3) innovation, (4) risk attitude and entrepreneurship, (5) owners-managers, and residual contributions. The theoretical foundations that support this research structure have been (1) the resource-based view, (2) pecking order theory, agency theory and trade-off theory, (3) the entrepreneurial orientation perspective, human capital theory and upper echelon theory, and (4) planned behaviour theory. Subsequently, we developed an integrative framework on which to base proposals of important avenues for future research. Thus, this review offers a thorough and comprehensive overview of this emerging research field.
https://openpolicyfinder.jisc.ac.uk/id/publication/8215
Keywords: Pequeñas y medianas empresas; Bibliometría; Educación financiera; Financial literacy